The portrayal of ICT in the media: a Malaysian scenario - Mohd Yusof Hj. Abdullah,; Fuziah Kartini Hassan Basri,; Mohd Safar Hasim,; Mat Pauzi Abd Rahman, (Universiti Kebangsaan Malaysian, 2009)
Malaysia, as a developing country, is gearing towards creating a network society. This is aimed at providing opportunities for the rakyat to actively participate in the economic, social and political spheres of the country via information and communication technology (ICT). As such the national mass media, government or private, have jumped on the bandwagon and increasingly placed ICT in their content. This paper discusses how media portray information on ICT and how the information is perceived by the rakyat. It is a descriptive discussion of a content analysis on selected print and electronic mass media in their depictions of ICT, and some selected findings from a survey on 1500 respondents throughout Malaysia. The purpose is to highlight the role of the media in the dissemination of information on ICT and how they help the government in popularizing and promoting the use of ICT towards the realization of the network society.